PERCEPTION AND PREFERENCES OF GOAT BREEDERS TOWARD LIVESTOCK INSURANCE - Wahyu Dyah Prastiwi; Miggie Handayani; Kustopo Budiraharjo; Hery Setiyawan (Hexagro Journal, 2021)
The paper explores goat breeders’ perception and preferences toward livestock insurance. The respondents of the study were goat breeders in Manunggal IV farmers’ group in Semarang Regency, Central Java Province. Descriptive analysis was used to illustrate the perception variables. The methodology was then followed by Conjoint analysis to explore the preferences of goat breeders toward livestock insurance based on three attributes. The study found that goat breeders have a negative perception toward livestock insurance product, although they are aware of climate change. The results showed that the preferences’ utility of flexible premium insurance, outbreak coverage, and less than 1-month claim process are the best option. Premium insurance cost is the most important factor in the livestock insurance product.Keywords: Conjoint analysis, livestock insurance, preferences.